Efektifitas Pembelajaran Sistem Daring (Online) Mata Kuliah Statistik Ekonomi Di Masa Pandemi - Novita, Novita (Diklat Review : Jurnal manajemen pendidikan dan pelatihan, 2020)
The period of the Covid 19 pandemic continues and do not know how long it will end, the world of education must continue to run, many methods are used to deliver lecture material for students. Especially in PTS, where PTS is very dependent on students for the sustainability of educational institutions, they continue to look for the best way to provide services to their students. One of the ways that is used is with an online system, this system in certain subjects, for example, economic statistics, becomes a relatively difficult system to implement. Therefore, in this study, a study was carried out to what extent the application of online systems was able to achieve learning outcomes that were ideally achieved by lecturers in teaching. This study used a descriptive descriptive method, in which a survey research was carried out by describing the achievement of learning economic statistics subjects to students. The questionnaire was conducted by assessing the responses of students receiving lectures using an online system during this pandemic. The data analysis technique uses descriptive techniques by comparing the reality with the ideal according to the concept. The results showed that the effectiveness of statistical learning with this online system had a positive and significant impact on student satisfaction in learning as well as increasing the enthusiasm for learning and the seriousness of students in learning statistics.